2007
DOI: 10.2175/193864707787976803
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Effect on the Phosphorus Uptake Activity of Phosphate Accumulating Organisms (Pao) in Pilot-Scale SBR and MBR Reactors

Abstract: Batch tests, performed to investigate the effect of nitrite on the P-uptake activity of biomass grown in pilot-scale SBR and MBR systems, showed that the nitrite has an inhibitory but reversible effect on the aerobic P-uptake activities of the SBR and the MBR biomass. The inhibitory effect was found more pronounced on the SBR biomass, in which the aerobic Puptake was inhibited by 65 % and 37 % at 10 mgNO 2 -N/l for the SBR and the MBR respectively. For the anoxic P-uptake activities, both the SBR and the MBR b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
3
Order By: Relevance
“…This observation agreed with findings of other researchers where nitrite inhibited the aerobic P uptake rate. Sin, et al (2008) reported that the aerobic P-uptake of the biomass from SBR was inhibited by 65% at nitrite concentration of 10 mg/L. Meinhold et al (1999 b) observed that when biomass exposed to higher concentration of NO 2 levels (roughly 8 mg N/L and greater) the aerobic P uptake was inhibited severely.…”
Section: Effect Of Nitrite On P Removalmentioning
confidence: 99%
“…This observation agreed with findings of other researchers where nitrite inhibited the aerobic P uptake rate. Sin, et al (2008) reported that the aerobic P-uptake of the biomass from SBR was inhibited by 65% at nitrite concentration of 10 mg/L. Meinhold et al (1999 b) observed that when biomass exposed to higher concentration of NO 2 levels (roughly 8 mg N/L and greater) the aerobic P uptake was inhibited severely.…”
Section: Effect Of Nitrite On P Removalmentioning
confidence: 99%
“…Currently, nitrite is considered a key intermediate to describe accurately the nitrification and denitrification processes, especially in some sidestream processes . Different approaches have recently been proposed for modeling nitrification and denitrification as two-step processes. ,,, As a consequence, modeling the nitrite behavior becomes essential for the description of other processes, including P uptake . Several studies with PAOs have confirmed that elevated concentrations of nitrite would negatively affect the activities of PAOs under either anoxic or aerobic conditions, although the different threshold values of inhibition were reported. ,,, Extended activated sludge models, including two-stage nitrification, two-stage denitrification and EBPR were developed to successfully predict the behavior of nitrite and nitrate …”
Section: Introductionmentioning
confidence: 99%
“…Un resumen de dichos modelos puede encontrarse en Sin et al, 2008. Algunos de estos modelos se centran en los procesos que tienen lugar en el tratamiento de aguas residuales con una alta carga de nitrógeno, como el sobrenadante de la línea de fangos digeridos anaerobiamente (Hellinga et al, 1999;Volcke, 2006 Sin et al, 2008 Corriente principal de planta Hao et al, 2002Moussa et al, 2005Kampschreur et al, 2007 Ambas Tabla 15. Principales modelos de nitrificación vía nitrito y agua residual en la que se han desarrollado.…”
Section: Revisión De Los Principales Modelos De Nitrificación Vía Nitunclassified
“…Estas diferencias se deben fundamentalmente a los supuestos realizados en cada caso y a la elección de las cinéticas de limitación por sustrato e inhibición. En la Tabla 16 se resumen las principales diferencias entre algunos de los modelos de nitrificación en dos etapas (Sin et al, 2008 …”
Section: Revisión De Los Principales Modelos De Nitrificación Vía Nitunclassified
See 1 more Smart Citation